New media and American politics - Davis, Richard (Oxford University Press, 1998)
New media have a major impact on all aspects of American political life. Presidential candidates appear in "electronic town meetings"; talk show hosts like Rush Limbaugh and G. Gordon Liddy lead dedicated bands of followers; tabloids break the Monica Lewinsky scandal with alarming speed. Traditional sources of information are increasingly altered by the presence of new media